2022
DOI: 10.3390/ma15175936
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Interactions in Wiegand Wires Evaluated by First-Order Reversal Curves

Abstract: Wiegand wires exhibit a unique fast magnetization reversal feature in the soft layer that is accompanied by a large Barkhausen jump, which is also known as the Wiegand effect. However, the magnetic structure and interaction in Wiegand wires cannot be evaluated by conventional magnetization hysteresis curves. We analyzed the magnetic properties of Wiegand wires at various lengths by measuring the first-order reversal curves (FORCs) and by evaluating the FORC diagram from a series of FORCs. In particular, we use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The coercive forces of the major hysteresis loops of the Wiegand wire are plotted in Figure 4 b, which are represented by the red dotted lines in Figure 6 . The comparative analysis demonstrated that the coercive force of the major hysteresis loop of the Wiegand wire with equal diameter was consistent with the maximum intensity of the FORC distribution, ρ [ 21 ].…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…The coercive forces of the major hysteresis loops of the Wiegand wire are plotted in Figure 4 b, which are represented by the red dotted lines in Figure 6 . The comparative analysis demonstrated that the coercive force of the major hysteresis loop of the Wiegand wire with equal diameter was consistent with the maximum intensity of the FORC distribution, ρ [ 21 ].…”
Section: Discussionmentioning
confidence: 92%
“…According to the magnetic structure of the 0.06 mm-diameter Wiegand wire, the inner layer was the hard layer and the outer layer was the soft layer. We analyzed the FORC diagrams of the Wiegand wires with diameters of 0.10, 0.14, 0.18, and 0.23 mm, and observed that their FORC diagrams were segmented into six or seven small regions with similar distributions, implying the existence of more than one coercivity component [ 21 ]. The distribution intensity of each small area of the FORC diagram increased with the increase in the diameter, as stated in Section 4.1 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations